2022
DOI: 10.3389/fimmu.2021.812176
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Structure-Based Screening of Potential T Cell Cross-Reactivities Involving Peptide-Targets From BCG Vaccine and SARS-CoV-2

Abstract: Although not being the first viral pandemic to affect humankind, we are now for the first time faced with a pandemic caused by a coronavirus. The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been responsible for the COVID-19 pandemic, which caused more than 4.5 million deaths worldwide. Despite unprecedented efforts, with vaccines being developed in a record time, SARS-CoV-2 continues to spread worldwide with new variants arising in different countries. Such persistent spread is in part ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Apart from these suggested mechanisms, it has been speculated that BCG vaccination might lower thresholds for T cell activation on account of the cytokine milieu that exists due to primed/trained monocytes ( 79 ). It should be noted that boosted T cell responses to COVISHIELD™ in individuals vaccinated with BCG might also be due to presence of cross-reactive epitopes in BCG and SARS-CoV-2 vaccines ( 80 ). Importantly, SARS-CoV-2 specific CD4+ T cell responses too have been demonstrated to be more robust compared to the CD8+ T cell response in the context of vaccination as well as infection ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these suggested mechanisms, it has been speculated that BCG vaccination might lower thresholds for T cell activation on account of the cytokine milieu that exists due to primed/trained monocytes ( 79 ). It should be noted that boosted T cell responses to COVISHIELD™ in individuals vaccinated with BCG might also be due to presence of cross-reactive epitopes in BCG and SARS-CoV-2 vaccines ( 80 ). Importantly, SARS-CoV-2 specific CD4+ T cell responses too have been demonstrated to be more robust compared to the CD8+ T cell response in the context of vaccination as well as infection ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…If early versions of so many genes evolved long ago in microbes, then essentially all life forms are constructed from closely related building blocks. This may explain why exposure to a very broad diversity of microorganisms, even if entirely harmless, can prime memory T cells that recognize previously unencountered pathogens such as HIV ( 13 ) or the COVID-19 virus ( 14 ).…”
Section: Evolution Of Relationship To Microbesmentioning
confidence: 99%
“…1 ) ( 35 , 36 ). Similarly, exposure to a very diverse range of microorganisms from the environment can prime memory T cells that by chance recognize even novel organisms that the individual has never previously encountered, such as HIV or the pathogen causing COVID-19 ( 13 , 14 ). Some of the types of organisms and information that microbial exposures supply to the immune system are listed in Fig.…”
Section: Evolution Of the Immune Systemmentioning
confidence: 99%
“…For example, a recent study involving SARS-CoV-2 found eight new BCG derived peptides with significant homology with NSP3 or NSP13 derived peptides of SARS-CoV-2 [155] , along with several similar studies involving in silico identification of multiple cross-reactive peptides between SARS-CoV-2 and BCG or Mycobacterium sp. antigens, which could drive heterologous immunity induced by BCG vaccination [156] , [157] , [158] , [159] , [160] . Furthermore, it was also found that the first stimulation of BCG-derived peptides could significantly enhance the immunoreactivity of CD4 + and CD8 + T cells to corresponding homologous peptides derived from SARS-CoV-2 [155] , [161] .…”
Section: Possible Mechanisms and Their Effects On Covid-19 Controlmentioning
confidence: 99%